Operations Management in the Era of Fast Fashion Technologies and Circular Supply Chains - Chan, Hau-Ling.; Ren, Shuyun; Liu, Na. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book reports the latest business practices, operations models, technologies and circular supply chain structure of the fast fashion companies and provides many important managerial insights on the sustainable operations management in the fast fashion era. Sustainability is a timely topic in both the academia and the business world. In the fast fashion era, there are considerable criticisms about its environmental pollution generated in the manufacturing and post-consumption processes. Over the past decades, many fast fashion companies, such as H&M, Zara, and Uniqlo, have implemented different sustainable programs to mitigate the negative impacts to the environment. Nowadays, the industry is moving one step further by addressing zero landfill through 3Rs principle (i.e., reducing, reusing and recycling), and pursuit of the circular supply chains. This book aims to reveal the exploratory, qualitative empirical and quantitative analytical studies on how to achieve the goal of being environmentally sustainable in the fast fashion era.
Part I Introduction and Exploratory Studies -- 1 Sustainable Operations Management in Fast Fashion Era: An Introduction (Hau-Ling Chan, Shuyun Ren and Na Liu) -- 2 Sustainability in Fast Fashion Era: The Jan 'N June Case (Daniela Candeloro) -- 3 Sustainable Practices in Fast Fashion (Na Liu and Fengling Xie) -- Part II Intelligent Fast Fashion Demand Forecasting -- 4 Fast Fashion Demand Forecasting Models: A Comparative Study (Yu Xiong and Lei Lin) -- 5 Impact of Search Index on Fashion Demand Forecasting- Panel Data Based Analysis (Zhicheng He, Xiong Yu and Shuyun Ren) -- Part III Theoretical Modelling Research, Reviews, and Research Agenda -- 6 Optimal Pricing, Green Advertising Effort and Advanced Technology Investment in Sustainable Fashion Supply Chain Management (Hau-Ling Chan, Shun-Mun Wong and Ka-Man Sum) -- 7 The Multi-Methodological Approach for Sustainable Operations Management in Fashion (Tsan-Ming Choi) -- 8 Overview and Research Agenda for Sustainable Operations Management in Fast Fashion Era (Hau-Ling Chan, Shuyun Ren and Na Liu).
Keywords: Production management; Management; Operations Management; Management